Revisiting surfactant protein D: an immune surveillance molecule bridging innate and adaptive immunity - Azra Shamim; Mughair Abdul Aziz; Faryal Saeed; Rekha Kumari; Ann Mary Joseph; Pretty Ponnachan; Uday Kishore; Uday Kishore; Khaled Masmoudi (Frontiers in Immunology)
Surfactant protein D (SP-D) is a C-type lectin that was originally discovered as a lung surfactant associated phospholipid recognising protein. It was originally shown to be of great importance in surfactant turnover and homeostasis in conjunction with another hydrophilic surfactant protein i.e. SP-A. In addition, it was found to agglutinate bacteria in suspension and likely a key defence molecule in the lungs. Since its early days of characterization in 1990s, SP-D has turned out to be a central player in the mucosal immunity as pulmonary as well as extrapulmonary innate immune molecule. The most exciting development has been characterization of its C-type lectin or carbohydrate recognition domain (CRDs) that exists in a homotrimeric form in native as well as recombinant versions. SP-D has a range of strategies to recognise pathogen-associated molecular patterns (PAMPs) and thus act as a soluble PAMP-recognizing receptor (PRR), and subsequent destruction of the pathogens directly, or indirectly via phagocytic cells. SP-D also recognizes a range of allergens, competes out with specific IgE antibodies, and downregulates histamine release by basophils and mast cells. These anti-microbial and anti-allergic properties of SP-D have been validated by in vivo murine models of infection and allergy. The SP-D gene deficient mice exhibit remarkable phenotypes where lungs are leaky, showing features of fibrosis and emphysema. One of the seminal discoveries in the field has been the observation that activated eosinophils (and other immune cells) can be induced into apoptotic pathways by SP-D. This raised the possibility that SP-D can be an innate immune surveillance molecule. Studies have revealed the ability of a recombinant fragment of human SP-D containing homotrimeric neck and CRD region to induce apoptosis via intrinsic as well as extrinsic pathways; in addition, it also seems capable of interfering with epithelial-to-mesenchymal transition. These studies have opened up enormous possibilities for setting up pre-clinical and clinical trials.